Resumo de artigo acadêmico: um estudo sobre organização retórica e sequências textuais - Andrade, Valter Zotto de (2017)
This thesis is situated in the Reading, Writing and Portuguese Language Teaching research line of the Program of Postgraduate Studies in Portuguese Language at the Catholic University of São Paulo (PUCSP) and its main subject is the rhetorical organization and the textual sequences of the academic article abstract genre. This study starts from the hypothesis that the rhetorical units of the genre under study are primarily constructed by narrative and descriptive sequences. Guided by this assumption, we defined the following research question: What textual sequences are predominant in the rhetorical units of an academic paper abstract? The general objective of this investigation is reflecting on the compositional structure of the academic paper abstract and the textual sequences which compose it. In order to achieve this general objective, the following specific goals were defined: 1º) describe the rhetorical organization of abstracts from academic papers selected from three journals specialized in Language; 2º) identify and analyze the textual sequences present in the abstracts which compose the corpus; 3º) relate the two approaches in order to identify which textual sequences are predominant in the rhetorical units composing the analyzed corpus. The theoretical foundation wherein this study is based on is comprised mostly by the assumptions of socio-rhetorical (BIASI-RODRIGES, 1998; SWALES, 1990, 2009; BHATIA, 1993, 2001; MILLER, 2012; BAZERMAN, 2011), Text Linguistics and Discourse Text Analysis (MARQUESI, 2004, 2016; BONINI, 2005; HERRERO CECILIA, 2006; PASSEGGI et al., 2010; ADAM, 2009, 2011; SILVA, 2012). The corpus is comprised by 30 academic paper abstracts from the Language field, of which we selected 11, whose analysis we present for exemplification purposes. We established as categories for analysis the rhetorical units, academic paper structure and textual sequences. From a methodology perspective, this research is descriptive, of a qualitative approach and interpretative basis. The obtained results show the predominance of narrative and descriptive sequences in the rhetorical units presented in the analyzed abstracts